Constitutional Court’s of the Russian Federation Impact on Public Property (Part 1) - S. I. Shulzhenko (Управленческое консультирование)
The article focuses on the main principles of public property as Constitutional Court of the Russian Federation formulates them. The author reveals actual problems of public property as a complex institution, including mainly constitutional, administrative, financial, and in a less degree civil law. There is a direct relation between public property, public finance, budget, legal regime of the territory concerned and citizens’ public rights. Establishment of a legal regime of the territory helps to preserve current public land and property usage and provides public rights. The ability of public property unilateral transfer to another level of public ownership is justified. Meantime in the context of specialized public housing stock problem the author suggests sensitive decision for the legal status of quarters as a specialized commercial housing stock. Legal positions of the Constitutional Court promote effective solution to the conflict within the community and provide guidance for the legislative and law-enforcement activity.